In vitro and in silico analyses of amino acid substitution effects at the conserved N-linked glycosylation site in hepatitis B virus surface protein on antigenicity, immunogenicity, HBV replication and secretion - Patcharin Tepjanta; Thammakorn Saethang; Kazuhito Fujiyama; Ryo Misaki; Ingorn Kimkong (PLoS ONE, 2025)
The "a" determinant, a highly conformational region within the hepatitis B virus large surface protein (LHBs), is crucial for antibody neutralization and diagnostic assays. Mutations in this area can lead to conformational changes, resulting in vaccination failure, diagnostic evasion, and disease progression. The "a" determinant of LHBs contains a conserved N-linked glycosylation site at N320, but the mechanisms of glycosylation in LHBs remain unclear. This study aimed to investigate the impact of amino acid substitutions at N320 on antigenicity, three-dimensional (3D) structures of LHBs, immunogenic epitopes, and HBV DNA levels. LHBs were mutated by substituting asparagine 320 with proline, cysteine, lysine, and glutamine. The reactivity of the mutants with antibodies was evaluated by western blotting and immunofluorescence staining. Results showed increased binding affinity in N320C, N320Q, and particularly N320P mutants compared to the wild type, likely attributed to conformational changes predicted by the I-TASSER server and further refined by the GalaxyRefine server. Analysis conducted using the IEDB server indicated that the N320P mutation increased the antigenic index, whereas the N320C mutation significantly decreased it. Conversely, the N320K and N320Q mutations exhibited minor effects on antigenicity. Our observations also identified N320P as a potential B-cell epitope and a binding epitope for MHC-I (T-cell epitope). Furthermore, mutating the conserved N-linked glycosylation site at position N320 to proline significantly increased the secretion of HBV DNA in virions. This study enhances our understanding of the impact of a single amino acid mutation at N320 on antibody interaction, LHBs conformation, immunogenicity, and HBV DNA replication. These insights hold promise for advancements in HBsAg detection and the development of vaccines against hepatitis B virus.